2009
DOI: 10.1186/1471-2466-9-49
|View full text |Cite
|
Sign up to set email alerts
|

Plasma CC16 levels are associated with development of ALI/ARDS in patients with ventilator-associated pneumonia: a retrospective observational study

Abstract: BackgroundDespite consensus criteria, diagnosing acute lung injury, or its more severe form acute respiratory distress syndrome (ALI/ARDS) remains challenging. Adding objective measures, such as plasma levels of biological markers could facilitate recognition of ALI/ARDS. This study was designed to assess and compare the diagnostic accuracy of biological markers for ALI/ARDS with ventilator-associated pneumonia (VAP).MethodsWe performed serial measurements of Clara cell protein (CC16), soluble receptor for adv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
58
3
2

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 68 publications
(68 citation statements)
references
References 36 publications
0
58
3
2
Order By: Relevance
“…ARDS patients in the present study had more than double the median values of CC16 when compared with non‐ARDS patients. While previous studies have demonstrated a relatively stable median CC16 value in normal controls (5‐7 ng/mL),12, 13 the median CC16 value of non‐ARDS patients in this study appeared to be higher (24.13±12.32 ng/mL). Some cases from the non‐ARDS patient group had developed pulmonary diseases such as pneumonia, which may have caused an elevated production of CC16 18.…”
Section: Discussioncontrasting
confidence: 93%
See 1 more Smart Citation
“…ARDS patients in the present study had more than double the median values of CC16 when compared with non‐ARDS patients. While previous studies have demonstrated a relatively stable median CC16 value in normal controls (5‐7 ng/mL),12, 13 the median CC16 value of non‐ARDS patients in this study appeared to be higher (24.13±12.32 ng/mL). Some cases from the non‐ARDS patient group had developed pulmonary diseases such as pneumonia, which may have caused an elevated production of CC16 18.…”
Section: Discussioncontrasting
confidence: 93%
“…The CC16 values of above 33.3 ng/mL statistically discriminated differentiates between ARDS and non‐ARDS patients, demonstrating a relatively high diagnostic accuracy. Although we did not compare the diagnostic value of CC16 with other biomarkers in this study, previous studies have demonstrated that CC16 had greater diagnostic capacity than surfactant protein‐D (SP‐D), Krebs von den Lungen‐6 (KL‐6), and soluble receptor for advanced glycation end‐products (sRAGE) for ARDS 13. A combination of CC16, SP‐D, and KL‐6 could provide enhanced efficacy in lung disease screening and diagnosis 14.…”
Section: Discussionmentioning
confidence: 99%
“…Data have been mixed with that of some authors showing strong correlations between plasma CC-16 levels and ARDS development [10,11], whereas others have shown poor or inverse correlations [12,14]. This may relate, in part, to the choice of control population, as CC-16 levels are also elevated in heart failure patients [14].…”
Section: The Epithelial Markersmentioning
confidence: 88%
“…Unfortunately, serum KL-6 levels are elevated in other respiratory diseases including interstitial pneumonitis, so may not be specific for ARDS in patients with underlying lung disease. Indeed, a study of critically ill patients with ventilator-associated pneumonia showed no difference in serum KL-6 levels between those who developed ARDS and those who did not [11].…”
Section: The Epithelial Markersmentioning
confidence: 95%
See 1 more Smart Citation